KRITERIA AGAMA DALAM PERDEBATAN (Pandangan Masyarakat Sumba Barat, Nusa Tenggara Timur) - Sulaiman Sulaiman (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
The conception of religion in Indonesia has various definitions that causes discriminatory behavior against religious believers, especially followers of local religions. This study aims to describe the views of the community in west Sumba, East Nusa Tenggara about the criteria of a religion that can receive services from the government including the views of the community can be categorized in two parties: the mainstream and non-mainstream parties. The mainstream party define religion as affiliated by the society in general namely Islam, Christianity, Catholicism, Hinduism, Buddhism and Confucianism. In this case, the elements of religion include God, prophets, holy scriptures, organizations, places of worship, and government recognition. This is different from the non-mainstream religious groups who formulated the criteria of religion that are not necessary in line with mainstream ones. Yet the most important thing for a religion is to have the belief system of the oneness of god, to have the system of rituals or religious practices, and to have formal religious institutions, and a recognition from the society proved by registering their religion to the government agencies. These two criteria of religion have become a unfinished debate until today.